2019
DOI: 10.1101/670091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stimulation augments spike sequence replay and memory consolidation during slow-wave sleep

Abstract: Newly acquired memory traces are spontaneously reactivated during slow-wave sleep (SWS), leading to the consolidation of recent memories. Empirical studies found that sensory stimulation during SWS selectively enhances memory consolidation and the effect depends on the phase of stimulation. In this new study, we aimed to understand the mechanisms behind the role of sensory stimulation on memory consolidation using computational models implementing effects of neuromodulators to simulate transitions between awak… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…This hypothesis further suggests the existence of some nonexplicit cortical conditions that determine cortical sensitivity to the stimulation (i.e., whether the stimulation would boost SOs dynamics, whether it would be completely ineffective, or even induce awakenings). In line with this hypothesis, recent analyses suggest that the amplitude of SO peaks may facilitate global synchronization of post-neuronal down-states, thereby enhancing the amplitudes of the resulting slow wave troughs (Navarrete et al, 2022;Torres et al, 2021;Wei et al, 2020). Congruently, we found that large and synchronous C1 and C3 events were increased by stimuli during large peaks of the SOs (with average amplitudes larger than +40 μV across all EEG channels, Figures 2e & 2f).…”
Section: Changes On Slow Wave Categories Induced By Classupporting
confidence: 88%
“…This hypothesis further suggests the existence of some nonexplicit cortical conditions that determine cortical sensitivity to the stimulation (i.e., whether the stimulation would boost SOs dynamics, whether it would be completely ineffective, or even induce awakenings). In line with this hypothesis, recent analyses suggest that the amplitude of SO peaks may facilitate global synchronization of post-neuronal down-states, thereby enhancing the amplitudes of the resulting slow wave troughs (Navarrete et al, 2022;Torres et al, 2021;Wei et al, 2020). Congruently, we found that large and synchronous C1 and C3 events were increased by stimuli during large peaks of the SOs (with average amplitudes larger than +40 μV across all EEG channels, Figures 2e & 2f).…”
Section: Changes On Slow Wave Categories Induced By Classupporting
confidence: 88%
“…Another major aspect of our work is the effect of sleep on the network and on the memories stored in it. The role played by sleep in memory consolidation has been widely studied from an experimental point of view [46,47], but only recently it has become the object of theoretical and computational modelizations [27,[48][49][50]. In our work, we investigated computationally the effect of slow oscillations on the structure and the performances of the network when the STDP plasticity is turned on.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al [21,42,43] tested several ways of closed-loop stimulation, including the protocol of Ngo et al [3], in a cellular level model. Their results showed that the correct spatio-temporal localization of stimuli could facilitate the replay of a cortical sequence associated with the stimulation site, pointing to the need for peaks nesting for strengthening the neural connections.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach to improving the stimulation paradigm that attempts to increase SP and SO events during SWS is the use of mathematical models of brain activity [20,21]. In this way, mechanistic insights about the generation of SP and SO activity can guide the search for a better stimulation that maximizes its efficacy.…”
Section: Introductionmentioning
confidence: 99%